Neutrophils drive pulmonary vascular leakage in MHV-1 infection of susceptible A/J mice - Gong, Henry H.; Worley, Matthew J.; Carver, Kyle A.; Goldstein, Daniel R.; Deng, Jane C. (Frontiers in Immunology, 2023)
Background Lung inflammation, neutrophil infiltration, and pulmonary vascular leakage are pathological hallmarks of acute respiratory distress syndrome (ARDS) which can lethally complicate respiratory viral infections. Despite similar comorbidities, however, infections in some patients may be asymptomatic while others develop ARDS as seen with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections for example. Methods In this study, we infected resistant C57BL/6 and susceptible A/J strains of mice with pulmonary administration of murine hepatitis virus strain 1 (MHV-1) to determine mechanisms underlying susceptibility to pulmonary vascular leakage in a respiratory coronavirus infection model. Results A/J animals displayed increased lung injury parameters, pulmonary neutrophil influx, and deficient recruitment of other leukocytes early in the infection. Moreover, under basal conditions, A/J neutrophils overexpressed primary granule protein genes for myeloperoxidase and multiple serine proteases. During infection, myeloperoxidase and elastase protein were released in the bronchoalveolar spaces at higher concentrations compared to C57BL/6 mice. In contrast, genes from other granule types were not differentially expressed between these 2 strains. We found that depletion of neutrophils led to mitigation of lung injury in infected A/J mice while having no effect in the C57BL/6 mice, demonstrating that an altered neutrophil phenotype and recruitment profile is a major driver of lung immunopathology in susceptible mice. Conclusions These results suggest that host susceptibility to pulmonary coronaviral infections may be governed in part by underlying differences in neutrophil phenotypes, which can vary between mice strains, through mechanisms involving primary granule proteins as mediators of neutrophil-driven lung injury.